Persistent Change in Livelihoods in Bhirgaun, Eastern Nepal (Geographical Journal of Nepal, 2011)
This paper deals with persistent change in livelihood and investigates how local people adapt to changing environment in Bhirgaun of Dhankuta district, eastern Nepal. The area offers a lot of resources; here I refer to the general term inherited property of indigenous communities for their survival over centuries. Out of total 12 settlements of Bhirgaun representing upper, middle and lower hills were selected. Data were acquired from 207 households by utilizing purposive sampling. The survey result indicated that agriculture is a mainstay of livelihoods of the people. The livelihood activities under different environmental conditions have undergone change with varying level of changes. For example, high level of changes is indicated in the upper, medium level of changes in the lower and low level of changes in the middle hills. Recently, vertical and horizontal connection outside the region creates both opportunities and constraints. But, their dependence on market varies widely from one place to another and among different societies.The Geographical Journal of Nepal, Vol. 8, 2010-2011: 73-82